Next‐generation sequencing in two cases of de novo acute basophilic leukaemia. Issue 14 (16th June 2021) - Shimizu, Takuya; Kondo, Tadakazu; Nannya, Yasuhito; Watanabe, Mizuki; Kitawaki, Toshio; Shindo, Takero; Hishizawa, Masakatsu; Yamashita, Kouhei; Ogawa, Seishi; Takaori‐Kondo, Akifumi
Abstract: Acute basophilic leukaemia (ABL) is a rare subtype of acute myeloid leukaemia (AML); therefore, few data are available about its biology. Herein, we analysed two ABL patients using flow cytometry and next‐generation sequencing (NGS). Two cell populations were detected by flow cytometry in both patients. In Case no. 1, blasts (CD34 +, CD203c −, CD117 +, CD123dim + ) and basophils (CD34 −, CD203c +, CD117 ±, CD123 + ) were identified, both of which were found by NGS to harbour the 17p deletion and have loss of heterozygosity of TP53 . In Case no. 2, blasts (CD33 +, CD34 +, CD123 − ) and basophils (CD33 +, CD34 +, CD123 + ) were identified. NGS detected NPM1 mutations in either blasts or basophils, and TET2 in both. These data suggest an overlap of the mutational landscape of ABL and AML, including TP53 and TET2 mutations. Moreover, additional mutations or epigenetic factors may contribute for the differentiation into basophilic blasts.